PECULIAR FEATURES OF ALKALINE-SILICATE THERMAL INSULATION MATERIALS - S. N. Leonovich; G L. Schukin; A. L. Belanovich; V. P. Savenko; S. A. Karpushenkov (Наука и техника)
The paper presents investigation results pertaining to peculiar features of thermal insulation material production and description of their property study. The production process presupposes  swelling of alkaline-silicate raw materials at temperature 300–500 °C of mixes, are presented.